Antithrombin activity as a significant predictor of early mortality in pulmonary embolism patients - Džudović, Boris; Džudović, Jelena; Subotić, Bojana; Obradović, Slobodan (Vojnosanitetski pregled, 2023)
Background/Aim. The role of antithrombin (AT) activity in predicting early mortality in patients with pulmonary embolism (PE), measured at an early stage of the disease, has not yet been investigated. Therefore, the aim of the study was to examine the predictive value of AT activity for all-cause 30-day mortality, measured in consecutive PE patients on admission to the hospital. Methods. This single-center clinical retrospective cross-sectional study followed consecutive patients with acute PE from 2014 to 2021. On admission to the hospital, venous blood was taken from patients for laboratory analyses including determination of AT activity. The basic parameters of the patients were recorded on admission, and through the univariate analysis, their connection with 30-day mortality was tested. The predictive significance of AT values for 30-day mortality was tested through quartile values by comparing the first quartile with all others together. Cox regression model analysis was used in the multivariate analysis where one parameter, marked as significant in the univariate analysis, was added to the basic model (AT, age, and risk affiliation in two groups). Results. A total of 378 PE patients were included in the study. The total all-cause 30-day mortality was 7.9% (30 patients). Patients with AT activity in the first quartile had significantly higher early mortality compared with those having AT activity in the other quartiles combined (log-rank p = 0.001). AT retained a significant predictive value for early mortality in the multivariate analysis despite the comorbidity present, which also significantly affected mortality. Conclusion. Low AT activity measured on admission in PE patients is a significant and independent predictor of 30-day mortality.
Keywords: antithrombins; mortality; prognosis; pulmonary embolism.